Default-name and tasting nudges increase salsify soup choice without increasing overall soup choice. (1st July 2019) - Broers, V.J.V.; Van den Broucke, S.; Taverne, C.; Luminet, O.
Abstract: Nudging is a popular behavior change technique but the conditions for its effectiveness have not been researched extensively. The current study aimed to test whether the effectiveness of nudging is limited to certain characteristics of the nudged product by focusing on a specific product (salsify soup) within a broader category (soups). Two parallel studies were conducted in two sandwich restaurants in a university setting at which a default-name nudge ("suggestion of the chef") and a tasting nudge were implemented aimed at increasing the choice for salsify soup using a non-randomized study design during 10 and 12 measurement days. The beta-regression model showed that the default-name nudge increased the proportion of customers that choose the salsify soup during intervention days compared to non-intervention days, p  < .001, OR: 1.70. The tasting nudge also increased the proportion of customers that choose the salsify soup from baseline to intervention, p  < .001, OR: 6.17 and from baseline to post-intervention, p  < .01, OR: 1.87, and decreased from intervention to post-intervention, p  < .001, OR: 0.30. Both nudges did not increase the choice for the overall category of soups. The results show that certain types of nudges are able to increase specific products of a category without increasing overall choice of a category in contrast to previous findings.